(untitled) (CIPEEX, 2025)
The CestaSync platform represents a major innovation in managing basic food basket deliveries. It offers unparalleled flexibility, handling everything from recipient registration to comprehensive reports generated by Artificial Intelligence. Beyond managing current baskets, CestaSync maintains a full history of all baskets distributed. It also includes a dedicated area for managing donations, enhancing overall efficiency. The platform empowers users to analyze and study data related to food baskets, facilitating evidence-based decision-making, optimizing resources, and increasing operational efficiency while mitigating risks. These features significantly enhance the customer experience and improve the platform’s impact on local communities. In early 2024, a severe flood in Rio Grande do Sul led to widespread donations, but the state lacked the technical capacity to manage them effectively. A well-designed system like CestaSync could streamline this process, improving both donation management and data analysis during such crises.